Knowledge Creation pada Industri Kecil dan Menengah : Dalam Tinjauan Kajian Pustaka secara Sistematis - Retno Indriartiningtias; Subagyo Subagyo; Budi Hartono (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2017)
The purpose of this paper is to review the research on knowledge creation in small and medium industries, to identify gaps in research that exist today as the direction of future research. The study was conducted by reviewing systematically at 9 articles in the field of knowledge creation in small and medium industries. Area of knowledge management in small and medium industries are still very rare, especially in the measurement of output and outcome results from the process of knowledge creation. In the process of knowledge creation there have been several studies but still generally in the form of exploratory research. Research to measure knowledge creation process with quantitative methods still exist. This study only uses an article published in Inside Emerald alone so it can not identify the research in the field of knowledge creation in small and medium industries in full. However, this study has contributed in terms of the direction on knowledge creation in small and medium industries to do in the future. Based on the author's understanding there has been no systematic systematic literature review in this field, published in scientific journals.